Implementasi Merdeka belajar Kampus Merdeka Melalui Pendampingan Orang dengan Gangguan Jiwa dalam Terapi Aktivitas Kelompok Membatik oleh Mahasiswa Korps Sukarela Palang Merah Indonesia - Huda, Alvin; Eka Septiyana Hidayantia, Veni; Yustina Suprihatining Tyasaa, Maria; Guntur, Ahmad (Satwika: Jurnal Pengabdian Kepada Masyarakat, 2023)
Negative stigma in society about people with mental disorders (ODGJ) leads to discriminatory behavior. One of the efforts that can be made by students is to implement the Independent Learning Campus (MBKM) program And The Seven Principles Of The International Red Cross And Red Crescent Movement. The aim of the program is to implement the MBKM program and the principle values ​​of the international red cross and red crescent movement by empowering PLWHA. The activity method is carried out on partners, namely puskesmas nurses, village officials, health cadres and ODGJ. Activities carried out within one month. By going through 4 processes, namely assessment, village community meetings, revitalization of the Posyandu Jiwa and therapy for batik group activities, evaluation of follow-up plans. And the result is that there are problems with health services in the community and ODGJ batik activities still need help in doing it so there is a need for ODGJ assistance in activities towards micro, small and medium enterprises and in the MBKM program there is an implementation mechanism carried out by universities, students and partners. The conclusion is that the MBKM Program through batik group therapy activities for ODGJ is very effective and has an impact on partners, institutions, and students in the learning process of humanitarian projects.